Challenges in curbing illegal orthodontics: a qualitative study on dental enforcement officers in Malaysia - Mohd Nor, Nor Azlida; Cheong, Joo Ming; Bahar, Aufa Dahlia; Zainal Abidin, Haznita; Kamarudin, Yasmin (Sciendo, 2023)
Background: Illegal orthodontics is on the rise, with ‘fake’ braces being reported mainly in South-East Asia. Health concerns have been raised despite ongoing efforts to increase public awareness. Objectives: To explore the perceptions of Dental Enforcement Officers from The Oral Health Legislation and Enforcement Section, Ministry of Health Malaysia regarding the challenges in managing complaints against ‘fake’ braces providers in Malaysia. Methods: Three focus group discussions were conducted involving twelve Dental Enforcement Officers (DEOs) who have managed complaints regarding illegal orthodontic practices over the past two years. Participants were asked about their actions in response to complaints and their perceptions of the challenges faced during the incidents. Information collection was concluded once data saturation was achieved. The interviews were transcribed and thematically analysed using NVIVO software. Results: The data identified six predominant themes which were: (1) A lack of resources; (2) Emotional strain on DEOs; (3) External support for illegal providers; (4) Difficulty in gathering information; (5) Complex planning and execution of raids; and (6) A lack of online regulation. Conclusion: The management of ‘fake’ braces activities is complicated and requires DEOs to work closely with various authorities for a successful outcome. This study may offer some insight into ways of overcoming these challenges.